Trends in Coronary Revascularization Procedures Among Medicare Beneficiaries Between 2008 and 2012. Issue 4 (27th January 2015) - Culler, Steven D.; Kugelmass, Aaron D.; Brown, Phillip P.; Reynolds, Matthew R.; Simon, April W.
<x xml:space="preserve">Abstract</x> Background— This study reports on the trends in the volume and outcomes of coronary revascularization procedures performed on Medicare beneficiaries between 2008 and 2012. Methods and Results— This retrospective study identifies all Medicare beneficiaries undergoing a coronary revascularization procedure: coronary artery bypass graft surgery or percutaneous coronary intervention (PCI) performed in either the nonadmission or inpatient setting. International Classification of Diseases, 9th Revision, Clinical Modification procedure codes (inpatient setting) and Current Procedural Terminology and Ambulatory Payment Classification codes (nonadmission) were used to identify revascularizations. The study population consists of 2 768 007 records. This study finds that the rapid growth in nonadmission PCIs performed on Medicare beneficiaries (60 405–106 495) has been more than offset by the decrease in PCI admissions (363 384–295 434) during the study period. There also were >18 000 fewer coronary artery bypass graft admissions in 2012 than in 2008. This study finds lower observed mortality rates (3.7%–3.2%) among Medicare beneficiaries undergoing any coronary artery bypass graft surgery and higher observed mortality rates (1.7%–1.9%) for Medicare beneficiaries undergoing any PCI encounter. This study also finds a growth in the number of facilities performing revascularization procedures during the study period: 268 (20.2%) more sites were performing nonadmission PCIs; 136 (8.2%) more sites were performing inpatient PCIs; and 19 (1.6%) more sites were performing coronary artery bypass graft surgery. Conclusions— The total number of revascularization procedures performed on Medicare beneficiaries peaked in 2010 and declined by >4% per year in 2011 and 2012. Observed mortality rates among all Medicare beneficiaries undergoing any coronary revascularization remained between 2.1% and 2.2% annually during the study period.